Comparing the clinical outcomes of single vs. systematic dual stenting strategies for unprotected left main bifurcation lesion: a systematic review and meta-analysis - Meng, Shuai; Kong, Xiangyun; Nan, Jing; Yang, Xingsheng; Li, Jianan; Yang, Shenghua; Zhao, Lihan; Jin, Zening (Frontiers in Cardiovascular Medicine, 2023)
Introduction The optimal percutaneous coronary intervention (PCI) strategy for coronary left main (LM) bifurcation lesions remains controversial. This meta-analysis compared the medium and long-term follow-up clinical outcomes of single vs. systematic dual stenting strategies of LM bifurcation lesions. Methods We systematically identified studies published within 5 years comparing single vs. systematic double stenting strategies for LM bifurcation lesions. The primary endpoint was medium-term (1 year) and long-term (at least 3 years) all-cause death. Secondary outcomes included major adverse cardiovascular events (MACEs), target lesion revascularization (TLR), overall occurrence of stent thrombosis (ST), cardiovascular (CV) mortality, and myocardial infarction (MI). Results Two randomized controlled trials and nine observational studies with 7,318 patients were included in this meta-analysis. In terms of the medium-term follow-up clinical outcomes, our pooled analysis showed that use of the systematic dual stenting strategy was associated with a lower ST risk (odds ratio [OR] = 0.43, 95% confidence interval [CI]: 0.20–0.89, P = 0.02) and cardiac death risk (OR = 0.43, 95% CI: 0.21–0.89, P = 0.02) compared to the single stenting strategy; there was no significant difference between the two strategies regarding rates of all-cause death, MACE, TLR, and MI. Patients with long-term follow-up showed comparable observed clinical outcomes between the two strategies. Most importantly, for patients with true LM bifurcation, the risk of all-cause death, ST, and CV mortality following the systematic dual stenting strategy was significantly lower than the single stenting strategy. Conclusions For patients with LM bifurcation lesions, both the systematic dual stenting strategy and single stenting strategy demonstrated comparable results in terms of all-cause mortality during medium-term and long-term follow-up. However, the systematic dual stenting strategy showed a tendency towards lower incidence of ST and CV mortality compared to the single stenting strategy during medium-term follow-up. Consequently, the systematic dual stenting strategy yielded superior clinical outcomes for patients with LM bifurcation lesions.